Muhammadiyah Sebagai Gerakan Pendidikan: Sejarah Eksistensi Perguruan Tinggi Muhammadiyah di Sulawesi Tenggara - Alifuddin, Muhammad (Institut Agama Islam Negeri Kendari, 2021)
This article presents an analytical description of the Muhammadiyah movement in the field of higher education services in Southeast Sulawesi. Data was garnered from in-depth interviews, observations and documents which were analyzed through the stages of data reduction, data presentation and drawing conclusions. The results of data analysis show that there are two main factors that move Muhammadiyah to establish universities in Southeast Sulawesi. First, internal factors such as moral awareness to build civilization through education. Second, external factors such as situational